PENGARUH AGRESIVITAS TRANSFER PRICING, PENGGUNAAN NEGARA LINDUNG PAJAK, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP PENGHINDARAN PAJAK - Suparna Wijaya; Fitriyan Dwi Rahayu (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2021)
This study examined the effect of transfer pricing aggressiveness, tax heaven, and institusional ownership on tax avoidance with tax audit as moderating variabel. The research object used 65 manufacturing companies listed on the Indonesia Stock Exchange in the 2015-2019 period, so the total observation is 325 samples. The results show that transfer pricing aggressiveness has a positive effect and institutional ownership has a negative effect on tax avoidance, while tax heaven has no effect on tax avoidance. In addition, moderation in tax audits is able to weakens the positive effect of transfer pricing aggressiveness on tax avoidance. However, tax audits does not weaken the positive effect of tax heaven and does not strengthen the negative effect of institutional ownership on tax avoidance.